Performance Comparisons and Dynamic Incentives - Meyer, Margaret A.; Vickers, John (Journal of Political Economy, 1997)
It is well known that comparative performance information can enhance efficiency in static principal-agent relationships by improving the trade-off between insurance and incentives in the design of explicit contracts. In dynamic settings, however, there may be implicit as well as explicit incentives, for example, managerial career concerns and the ratchet effects in regulation. The authors show that the dynamic effects of comparative performance information on implicit incentives can either reinforce or oppose the familiar (static) insurance effect and in either case can be more important for efficiency. The overall welfare effects of comparative performance information are thus ambiguous and can be characterized in terms of the underlying information structure. Copyright 1997 by the University of Chicago.